2013
DOI: 10.3390/w5020747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Timber Harvesting with Best Management Practices on Ecosystem Metabolism of a Low Gradient Stream on the United States Gulf Coastal Plain

Abstract: Stream metabolism can be used as a measure of freshwater ecosystem health because of its responsiveness to natural and anthropogenic changes. In this study, we used stream metabolic rates to test for the effects of a timber harvest with Louisiana's current best management practices (BMPs). The study was conducted from 2006 to 2010 in a loblolly pine (Pinus taeda) stand in north-central Louisiana, USA, 45 ha of which was clear cut harvested in the summer of 2007. Dissolved oxygen (DO), water temperature, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Stream temperature change due to forest harvest has been widely studied at both local scales (e.g. Gray and Edington, ; Brown and Krygier, ; Baillie et al ., ; Gomi et al ., ; Gravell and Link, ; Groom et al ., , ; Janisch et al ., ; Rex et al ., ; DaSilva et al ., ; Kibler et al ., ) and downstream scales (Brown et al ., ; Caldwell et al ., ; Zwieniecki and Newton, ; Story et al ., ; Rutherford et al ., ; Cole and Newton, ; Garner et al ., ; Johnson and Wilby, ). This abundance of studies reflects the concern over stream temperature impacts to aquatic ecosystems and has led to the evolution of stream protection rules for managed forests (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Stream temperature change due to forest harvest has been widely studied at both local scales (e.g. Gray and Edington, ; Brown and Krygier, ; Baillie et al ., ; Gomi et al ., ; Gravell and Link, ; Groom et al ., , ; Janisch et al ., ; Rex et al ., ; DaSilva et al ., ; Kibler et al ., ) and downstream scales (Brown et al ., ; Caldwell et al ., ; Zwieniecki and Newton, ; Story et al ., ; Rutherford et al ., ; Cole and Newton, ; Garner et al ., ; Johnson and Wilby, ). This abundance of studies reflects the concern over stream temperature impacts to aquatic ecosystems and has led to the evolution of stream protection rules for managed forests (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These pollutants, due to their low aqueous solubility and strong hydrophobic character, could be transported or deposited with sediment-associated phases [51,52], which may be a new but urgent warning to portable water supply and human health in the river basin given the projected rising of erosion and sediment yield. Studies conducted in forested headwaters also found that, when excess sediment reaches water bodies, organic matter or oxidizable inorganic nutrients could increase sediment oxygen demand (SOD) in the streambed [53][54][55], which could cause dissolved oxygen depletion [54,55] and stream metabolism [56].…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…diffuse effects such as leaching, temperature increase caused by deforestation) and only one (2% = 1) studied its point impact, (Rosa et al, 2013, studying effects of a fish farm effluent). Among eight other studies in the category agriculture, four evaluated the effects of deforestation not related to agricultural activity (Houser et al, 2005;Mulholland et al, 2005;Clapcott & Barmuta, 2010;O'Driscoll et al, 2016), three studied the effects of agroforestry management (Silva et al, 2013;Carlson et al, 2014;Pearce & Yates, 2015), one evaluated the effects of pesticides and salinity (SchĂ€fer et al, 2012) and other the effects of exotic arboreal vegetation in grassland natural areas (Riley & Dodds, 2012) ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%